TANGGUNG JAWAB ORGAN PERSEROAN TERBATAS DALAM KEPAILITAN PERSEROAN TERBATAS (Solusi, 2023)
A limited liability company as a legal institution which is an association of capital in carrying out its daily business activities is controlled by three main organs that are authorized by the corporation law to run the company, namely the general meeting of shareholders, directors, and commissioners. In the day to day management of the company, the directors will be fully responsible. the responsibilities of the directors are not only limited to the day to day management of the company, but the directors are also responsible for bankruptcy that befalls the company caused by their mistakes or negligence. Likewise, other company organs are also responsible if the bankruptcy of the limited liability company is caused by their mistakes or negligence.